Peran Dasar-Dasar Kependidikan dalam Pengembangan Karakter dan Kepribadian Siswa - Rozan Arkhan Daifullah; Hashim Al Ash Hari; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Developing students' character and personality is the main goal of education that requires special attention. This is becoming increasingly important in the era of globalization and digitalization which brings great challenges in maintaining moral and social values ​​among the younger generation. The basics of education, which include philosophical, psychological, sociological and cultural foundations, have a significant role in forming students' characters with integrity, empathy and discipline. This article aims to analyze the role of each educational foundation in supporting the formation of students' character as a whole and in depth. Using a descriptive qualitative research method through literature study, this research examines the contribution of each foundation comprehensively. The research results show that the philosophical foundation provides guidance on the basic values ​​and principles that students must have; psychological foundations help adapt educational approaches to the mental and emotional development of students; sociological foundations of creating a positive and supportive social environment; and cultural foundations strengthen local cultural identity in students. This article contributes to providing an integrative, holistic approach to character education, especially in Indonesia, with the hope of providing richer insight for educators in designing effective learning strategies in developing students' character and personality in accordance with local and national values.